Low-limit acetone detection system combining quantum conductance and capacitance signal analyses derived from oxidized single-layer graphene - Hostert, Leandro [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier, 2023)
This paper introduces a cutting-edge sensing technology that combines quantum conductance and capacitance signal analyses extracted from impedance measurements for the detection of acetone in gaseous or liquid forms. The electrochemical oxidation of a single-layer graphene (SLG) was employed through chronoamperometry, resulting in enhanced acetone sensing capability, enabling potential diabetes control using acetone as a marker. The modified SLG exhibits a distinct impedance response, offering access to the concentration of oxidized groups as a secondary signal in the capacitive Nyquist diagram. This methodology involves measuring the quantum conductance and capacitance of oxidized single-layer graphene by the Quantum Rate theory and applying these highly sensitive signals to measure acetone. Significantly low limits of detection were attained (∼ 0.13 nM). This study confirms that measuring the quantum properties of chemically modified graphene layers can be used to track environmental changes caused by different acetone concentrations. The findings reported here constitute a proof-of-concept that rightly modified 2D-carbonaceous materials can serve as effective analytical and sensing tools for the detection of acetone in the medical field of diabetes management.
Keywords: Acetone sensing; Diabetic control; Electrochemical transducer methods; Modified graphene; Quantum capacitance; Quantum mechanical sensing mechanism; Quantum rate